Inland shell midden site-formation: Investigation into a late Pleistocene to early Holocene midden from Trang An, Northern Vietnam - Rabett, R.; Appleby, J.; Blyth, Alison; Farr, L.; Gallou, A.; Griffiths, T.; Hawkes, J.; Marcus, D.; Marlow, L.; Morley, M.; Tan, N.; Son, N.; et al. (Pergamon-Elsevier Science Ltd, 2011)
Over the course of the past two decades there has been growing research interest in the site formation processes of shell middens. This stands along-side and is being used to inform cultural, dietary and palaeo-environmental reconstructions. Just as midden site formation processes have turned out to be many and varied, however, the kinds of shell-bearing sites that past human communities created are likely to have been no less diverse. Subsuming such sites under a single category – shell middens –normalises that variation and may lead to the misinterpretation of site function. The greater part of research in this field also continues to focus on coastal shell middens; comparatively little attention has been paid to middens containing freshwater and especially terrestrial molluscs from hinterland locations. As a result, much of the current understanding about shell-midden sites carries a spatial as well as a functional bias. This paper hopes to contribute towards discussion on both fronts. It presents a detailed examination of the formation processes that went into the creation of a land snail-dominated late- to post-glacial midden from northern Vietnam, and considers the role that it may have played in the early settlement of this area. The data presented comes from ongoing archaeological excavations at Hang Boi, a cave located in the sub-coastal karstic uplands of Trang An park, in the Vietnamese Province of Ninh Binh.